2019
DOI: 10.1016/j.scitotenv.2019.02.317
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural soil organic carbon stocks in the north-eastern Iberian Peninsula: Drivers and spatial variability

Abstract: Highlights SOC stocks were modelled using legacy data, environmental factors and geostatistics. The importance of SOC stock drivers differed in the top and subsoil. Effects of drivers on agricultural SOC stocks vary spatially at the regional scale. SOC stocks in Catalan agricultural soils contain 4.88 ± 0.89 kg/m 2 .  A baseline framework was established to design climate change mitigation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 51 publications
3
28
1
2
Order By: Relevance
“…The contribution of the root system to total plant carbon (C) storage can range from 9 to 26%, and total C storage in the vineyard can range from 5.7 to 7.2 t C/(ha/year) (Brunori et al 2016). Thus, vineyard soils and root systems can positively contribute to the mitigation strategies to manage climate change by increasing soil carbon storage (Funes et al 2019).…”
Section: Water Stressmentioning
confidence: 99%
“…The contribution of the root system to total plant carbon (C) storage can range from 9 to 26%, and total C storage in the vineyard can range from 5.7 to 7.2 t C/(ha/year) (Brunori et al 2016). Thus, vineyard soils and root systems can positively contribute to the mitigation strategies to manage climate change by increasing soil carbon storage (Funes et al 2019).…”
Section: Water Stressmentioning
confidence: 99%
“…In general, the mean SOC stocks decreased by 35−47% from 0-20 cm to 20-40 cm and by 25−33% from 20-40 cm to 40−60 cm. Other studies, such as Conant et al [28] in the southeastern United States, Li et al [43] in southwestern China, Tsozué et al [44] in central Africa, Funes et al [33] in north-eastern Spain, Chen [45] in central Taiwan, and Parras-Alcántara et al [46] in southern Spain, have also reported a decrease in SOC with depth.…”
Section: Depthwise Distribution Of Soil Organic Carbonmentioning
confidence: 86%
“…For example, mean SOC stocks were 1.7 ± 0.18 to 2.5 ± 0.24 kg/m 2 at 0−20 cm, 1.1 ± 0.08 to 1.3 ± 0.18 kg/m 2 at 20−40 cm, and 0.8 ± 0.14 to 0.9 ± 0.15 kg/m 2 at 40−60 cm. The range of SOC stocks in the three fields are comparable to other croplands studies, such as those conducted in Ohio, United States (mean: 0.41-2.24 kg/m 2 ) [40] and southern Germany (mean: 2.0-2.9 kg/m 2 ) [41], but lower than croplands in western Minnesota, United States (mean: 3.27 kg/m 2 ) [42], north-eastern Spain (mean: 3.5-14.7 kg/m 2 ) [33] and western Australia (mean: 3.1 kg/m 2 ) [6]. In general, the mean SOC stocks decreased by 35−47% from 0-20 cm to 20-40 cm and by 25−33% from 20-40 cm to 40−60 cm.…”
Section: Depthwise Distribution Of Soil Organic Carbonmentioning
confidence: 89%
See 1 more Smart Citation
“…Based on evidences from Germany, Vos et al [22] demonstrated that agronomic management can increase the carbon sink capacity of soil surface. Funes et al [23] discovered that the organic carbon stock of surface soil is mainly influenced by climate, soil texture, and agricultural variables, while that of bottom soil is mainly affected by soil texture, clay content, soil type and bedrock depth. Hertwich and Peters [24] calculated the carbon footprint of Luxemburg and 72 other countries, using the multi-regional input-output (MIRO) model.…”
Section: Introductionmentioning
confidence: 99%